Review : Flywheel Energy Storage for Use in Renewable and Distributed Generation - Aditya Rachman; Muhammad Umair; Muhammad Hasbi (Jurusan Teknik Mesin, Universitas Halu Oleo, 2016)
The aim of this paper is to discuss the use of flywheel energy storage for the renewable and distributed generation. This paper also figures the details of a connection of the flywheel energy storage system to a stand-alone PV solar system connected to a remote load. The methodology of generating this paper is literature studies. This paper is constructed into following sections: the renewable energy, the distributed generation, the solar energy, the energy storage, the flywheel energy storage, the use of energy storage and the connection of flywheel energy storage system into renewable power.